Mali : Selected Issues. (IMF Staff Country Reports; Country Report, 2008)
The cotton sector in Mali is facing major challenges to overcome, with low export prices, technical hurdles, and a poorly performing state-owned cotton ginner. Some reforms, most notably with regard to the setting of the farmgate procurement price, have already been undertaken, but more is needed to put the sector on a sound financial footing. It is vital that the production process be modernized and the ginner profoundly reformed if cotton is to play a major role in poverty reduction in rural Mali.